Trend Analysis Variations and Relation Between Discharge and Rainfall: a Study on Kushiyara River - Uddin, ME; Akter, SA; Uddin, MJ; Diganta, MTM (Journal of Environmental Science and Natural Resources, 2018)
Water resources and rivers play a very important role in economy and agriculture. But due to climate change and improper management, water resources are losing the natural discharge capacity from upper stream. This study was under taken to find out the trends and variability of rainfall and discharge at two stations of the Kushiyara River. Rainfall and discharge data Daily time series data of stream flow or discharge at Sheola (1976 to 2007) and Sherpur (1982 to 2007) and observed discharge data in certain interval from 2008 to 2016 have been analyzed in this study. For trend analysis, Mann-Kendall Test (MK) and Sen’s Slope Estimator method were used as non-parametric test and relationship assessment was done by undertaking Pearson’s Coefficient of Correlation. Annual discharge at Sheola and Sherpur station showed downward trend and maximum discharge was found downward trend at both stations. In Mannkendall test and Sen’s Slope Estimator method showed downward trend in most cases. Climate change and improper land management may have influenced the present condition. J. Environ. Sci. & Natural Resources, 10(2): 121-132 2017